Penataan ruang wilayah agropolitan Kabupaten Banjarnegara berbasis keberlanjutan fungsi lahan: studi kasus Kabupaten Banjarnegara - Aryanti, Dela Almira (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: The development of the Banjarnegara Regency area is planned as an agropolitan area. However, land use is still unsustainable, thereby threatening the sustainability of natural capital that can be utilized for the development of the agropolitan system. Research was carried out to determine and analyze the existence of land use that is not in accordance with the functional designation of the area. Metode: Findings: A Geographic Information System (GIS) is used to process and analyze spatial data, and then the data is analyzed descriptively, both quantitatively and qualitatively. It was found that there was 147,421.89 ha (50.13%) of land use appropriate to the area's function and 49.86% of land use not in accordance with the area's function. It is estimated that land use that is not suitable for its function is driven by aspects of the sub-district's superior commodities, the sub-district's physical geographic location, and population growth. Conclusion: It is concluded that further efforts are needed in spatial planning, monitoring, and enforcement, as well as other efforts to reduce land use that is not in accordance with the function of the area, in order to achieve the sustainability of the agropolitan system in Banjarnegara Regency.